TENDENSI PENGGUNAAN KAMERA POLAROID DI KALANGAN REMAJA - Fornia, S.I.Kom, M.I.Kom, Fornia, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2022)
The far and wide utilization of moment simple cameras as of late is a fascinating peculiarity. Photography is utilized as a position of articulation by its clients to show their reality in internet based media. Subtitles are one of the significant things here, for example, inscriptions as the hashtags 35mm